Chickpea flour and soy protein isolate interacted with κ-carrageenan via electrostatic interactions to form egg omelets analogue. (September 2022) - Lu, Zhou; Lee, Pin-Rou; Yang, Hongshun
Abstract: In recent years, demand for the plant-based egg substitutes has increased significantly, especially in Singapore, a country seeking for innovative food sources imminently. In the current study, chickpea flour, soy protein isolate, shortening, baking powder, mono, diglyceride, transglutaminase, potassium chloride, flour, and hydrocolloids (κ-carrageenan (κ-C) or gellan gum (GG)) were used to develop the eggless omelets. A formulation comprising 0.3% κ-C (0.3κ-C) best matched the physiochemical properties of egg, in terms of hardness (4437 vs. 4614 g), specific volume (1.24 vs. 1.19 cm 3 /g), and gel strength (19.3 vs. 17.5 kPa). This could be attributed to the highest synergistic κ-C-protein interactions in 0.3κ-C, along with the most homogeneous gel structure observed under confocal laser scanning microscopy (CLSM). The addition of 0.1% κ-C induced more κ-C-protein interactions than the one without hydrocolloids, but such increase was not as dominant as 0.3κ-C. When the κ-C concentration reached 0.5%, however, the rheological synergism decreased while the electrostatic interactions increased; that signifies the increased κ-C-κ-C interactions. Contrastingly, a segregated GG-protein interaction occurred in all GG systems, as indicated from synergism and CLSM images. These differences in interactions and structures affected the macroscale properties of our plant-based egg products, explaining the different physiochemical properties among them. A schematic diagram was therefore proposed to build connections between physiochemical properties, interactions, and structure. Graphical abstract: Image 1 Highlights: Plant-based egg with 0.3% κ-carrageenan (κ-C) matched the liquid egg best. Synergy between 0.3% κ-C & proteins and the uniform gel structure caused the match. Addition of 0.1% or 0.3% κ-C formed a 3D network with proteins filled by starch. Adding 0.5% κ-C replaced part of κ-C-protein interactions by κ-C-κ-C. Bi-continuous gel structure was observed in gellan gum gels.